Konsep Uang dalam Perspektif Islam - Muawanah (STEI Kanjeng Sepuh Gresik Jawa Timur, 2020)
At the beginning of civilization, humas fulfill all their needs independently. Because the current needs are still very simple. As the number of people grows and civilization progresses human interaction increases ang the increasingly diverse needs begin to require each other to meet their needs. At this satge , people are still bartering ( exchhanging goods), but this stage is felt to be less effective because of the increasinggly complex needs tahat cause constrants in making exchanges, namely the difficulty in obtaining the desired goods ao servise. To overcome the obstacles that arise due to the barter system of a commodity that can be used as a more effective and efficient means of exchange, namely “money”.